Marketing Communication Barriers in Computer Mediated Communication with Chat Features in E-commerce Applications - Marshelia Gloria Narida (Jurnal Spektrum Komunikasi, 2023)
The role of media connected to the internet has resulted in many changes, especially in the communication process through this media. Communication carried out through e-commerce is a form of computer-mediated communication, abbreviated as CMC, which is a communication process between two or more people via digital or computerized channels. This was stated by Carr (2021:4) that CMC is a process of exchanging meaning between two or more humans via digital channels. Barriers to marketing communication in CMC that occur through the seller's chat feature on the Shopee application show that there is the use of more than one account by the buyer, there is paralanguage in communication in the form of information from the seller to the buyer, the use of emoticons and emojis and stickers as communication which is considered a representation of feelings in nature. temporary or small talk, light interactions in the form of words of encouragement from buyers to sellers, phatic communication, communication that moves using other applications, information extraction carried out by sellers by looking for information about buyers who make large purchases, limited identification because only can see the name the buyer uses and how the buyer uses words or sentences in the conversation text and does not use the real name on the buyer's account.